KETERLAMBATAN LAPORAN AUDIT: INTERAKSI ANTARA FAKTOR INTERNAL PERUSAHAAN DAN KONSENTRASI KEPEMILIKAN SEBAGAI PEMODERASI - Alienta, Angelin; Tanujaya, Kennardi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025, 2025)
This study is motivated by the high incidence of delayed audit report submissions among property sector companies listed on the Indonesia Stock Exchange, which hinders stakeholder decision-making. The aim of this research is to analyze the factors influencing these delays, such as the impact of COVID-19, the role of internal audit, board independence, board size, and board meeting frequency. The study employs a quantitative approach using secondary data from the financial statements and annual reports of 47 companies from 2018 to 2022, analyzed through Moderated Regression Analysis. The results reveal that COVID-19 has a significant positive relationship with audit report delays, while the internal audit function has a significant negative relationship. The variables of board independence, board size, and board meetings, as well as the moderating effect of ownership concentration, are found to be insignificant. The findings emphasize the importance of internal audits in expediting audit reporting. The implications of this study suggest that companies need to strengthen internal audit functions and improve governance practices to reduce delays.